Election IAPSM UPUK 2016 - IAPSMUPUK, Secretary (Indian Journal of Community Health, 2016)
As per the constitution of IAPSM UPUK, all the members of IAPSM UPUK are hereby informed that Nomination Form for the election of Office Bearers of IAPSM UPUK is now available on the official website (www.iapsmupuk.org). The interested candidates can send their duly filled nomination form for the election of the following posts of IAPSM UP & UK state chapter for the session 2017 – 2018. Secretary: 01 Post Vice - President: 01 Post Chief Editor: 01 Post Executive Member: 09 Posts (Six from UP & three from UK) The eligibility criteria for the posts are given in the constitution of IAPSM UPUK. The last date of nomination for the above posts is 30th August 2016 and the last date of withdrawal of nomination is 10th September 2016. Nominations should be sent to secetaryiapsmupuk@gmail.com before the deadline. Candidates seeking election for the post of Secretary/ Chief Editor/Vice - President should send a demand draft of Rs. 1000/- and those for the post of the members of executive committee of governing council Rs. 500/- along with the duly filled nomination form. The details of the nomination fee and its mode of payment etc are given in the prescribed nomination form, which can be downloaded from the official website of IAPSM UPUK state chapter (www.iapsmupuk.org). For conducting fair elections, Prof. J. V. Singh (MZN) has been appointed by the Governing Council as Chief Election Officer. I hope this democratic way of electing our office bearers of IAPSM UP & UK will strengthen our association many fold. The elections will be held on the first day of IAPSM UPUK conference i.e., on 15th Oct’ 2016 during the General Council Meeting (GBM). I look forward to have active participation and cooperation all over.